FORMAL METHODS OF SUPPORT OF REORGANIZATION OF BUSINESS PROJECTS - Georgy N. Kalyanov (Статистика и экономика)
The article describes a set of methods that allow keeping a formal investigation of business processes of enterprises and carrying out their functional-structural design, testing and verification.